HigB of Pseudomonas aeruginosa Enhances Killing of Phagocytes by Up-Regulating the Type III Secretion System in Ciprofloxacin Induced Persister Cells - Li, Mei; Long, Yuqing; Liu, Ying; Liu, Yang; Chen, Ronghao; Shi, Jing; Zhang, Lu; Jin, Yongxin; Yang, Liang; Bai, Fang; Jin, Shouguang; Cheng, Zhihui; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
Bacterial persister cells are dormant and highly tolerant to lethal antibiotics, which are believed to be the major cause of recurring and chronic infections. Activation of toxins of bacterial toxin-antitoxin systems inhibits bacterial growth and plays an important role in persister formation. However, little is known about the overall gene expression profile upon toxin activation. More importantly, how the dormant bacterial persisters evade host immune clearance remains poorly understood. Here we demonstrate that a Pseudomonas aeruginosa toxin-antitoxin system HigB-HigA is required for the ciprofloxacin induced persister formation. Transcriptome analysis of a higA::Tn mutant revealed up regulation of type III secretion systems (T3SS) genes. Overexpression of HigB increased the expression of T3SS genes as well as bacterial cytotoxicity. We further demonstrate that wild type bacteria that survived ciprofloxacin treatment contain higher levels of T3SS proteins and display increased cytotoxicity to macrophage compared to vegetative bacterial cells. These results suggest that P. aeruginosa accumulates T3SS proteins during persister formation, which can protect the persister cells from host clearance by efficiently killing host immune cells.